Synthesis and Characteristics of Two Component Polyurethane Coatings Based on Epoxy Polyol with Polyisocyanate - Tennis Anthuvan, J.; Paruthimal Kalaignan, G.; Joseph Vincent, B. (Asian Journal of Chemistry, 2011)
Polyurethane coatings are formed from a chemical reaction between a polyol and a polyisocyanate hardener. Epoxy polyol resin was synthesized by reacting epoxy resin (diglicidyl ether of bisphenol A type), diethanolamine, cellosolve acetate and xylene at reflux tempe-rature 60-70 ºC for 6 h. Two component polyurethane coatings were prepared by blending of epoxy polyol and hexamethylene diisocyanate (HDI) hardener. By keeping the ratio of epoxy polyol consistent and by changing the ratio of hexamethylene diisocyanate from 0.80-1.20, a total of seven types of experiments were conducted. All these experiments were based on the solid contents of the hydroxyl equivalent weights of epoxy polyol and isocyanate equivalent weight of hexamethylene diisocyanate. After the film coated with the prepared polyurethane coatings, various physical properties and mechanical properties were measured and compared. The electrochemical impedance spectroscopy (EIS) was used for the characterization of the coated film. The formation of the polyol was supported by FTIR spectral data.